Novel design of a multitube microbial fuel cell (UM2FC) for energy recovery and treatment of membrane concentrates - Koroglu, Emre Oguz; Baysoy, Derya Yilmaz; Cetinkaya, Afsin Y.; Ozkaya, Bestamin; Cakmakci, Mehmet (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
A two-stage treatment process, consisting of a flat sheet membrane system and a novel upflow multitube microbial fuel cell ((UMFC)-F-2), was investigated to simultaneously treat concentrate streams-as well as produce electricity. This study tested the treatment of the retained part (i.e membrane concentrate) of the membrane process and electricity production using an air-cathode (UMFC)-F-2 inoculated with sediment sample collected from Golden Horn, Istanbul. The electrochemical behaviors were investigated using electrochemical methods to identify how membrane concentrates effects the reactor performance. The treatment of domestic wastewater was performed using a lab-scale cross-flow filtration apparatus with a UH050 membrane and the chemical oxygen demand (COD) removal efficiency as a result of membrane treatment was 87%. Then the (UMFC)-F-2 was fed sequentially from the feed tank when desired retained ratios (25% and 50%) observed. The maximum power density obtained was 25.138 mW m(-2) in the 50% concentrate or a volume concentration ratio (VCR) of 2 fed (UMFC)-F-2 which was 244% higher than that achieved using raw wastewater (7.303 mW m(-2)) and COD removal was >65% in (UMFC)-F-2. The contribution of different resistances such as ohmic, charge transfer and mass transfer resistances of the reactor under different stages was ascertained through the measurements using electrochemical impedance spectroscopy (EIS) and the results showed that an increasing organic loading reduced the internal resistance and enhanced power. On the whole, study reported new findings such as a new treatment technology for membrane concentrate treatment and gives insight to literature on reactor design. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: (UMFC)-F-2; Electrochemical impedance spectroscopy; Internal resistance; Voltage losses; Membrane concentrate; WASTE-WATER TREATMENT; IMPEDANCE SPECTROSCOPY EIS; ELECTRICITY-GENERATION; BIOELECTRICITY GENERATION; TECHNOLOGY; OPERATION; SYSTEMS; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels